2019
DOI: 10.1155/2019/2512687
|View full text |Cite
|
Sign up to set email alerts
|

High-Fat Diet Aggravates the Intestinal Barrier Injury via TLR4-RIP3 Pathway in a Rat Model of Severe Acute Pancreatitis

Abstract: Objective. For patients with severe acute pancreatitis (SAP), a high body mass index (BMI) increases the possibility of infection derived from the intestine. In this study, we evaluate whether TAK242 can alleviate severe acute pancreatitis-associated injury of intestinal barrier in high-fat diet-fed rats. Methods. A SAP model was established by retrograde injection of 5% sodium taurocholate into the biliary-pancreatic duct. Thirty Sprague-Dawley (SD) adult rats were randomly divided into five groups: standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…Among all TLRs, the ligand of TLR4 is lipopolysaccharide, a cell wall component of Gram-negative bacteria. It has been confirmed that TLR4 is closely related to acute intestinal injury and intestinal infection [24]. Consistent with previous studies, in our study, we found that TLR4 levels were remarkedly decreased in serum, intestinal and lung tissues of rats with acute intestinal injury, which were ameliorated by emodin treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Among all TLRs, the ligand of TLR4 is lipopolysaccharide, a cell wall component of Gram-negative bacteria. It has been confirmed that TLR4 is closely related to acute intestinal injury and intestinal infection [24]. Consistent with previous studies, in our study, we found that TLR4 levels were remarkedly decreased in serum, intestinal and lung tissues of rats with acute intestinal injury, which were ameliorated by emodin treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, the caerulein-induced AP model and PDL-induced SAP are essentially caused by hypersecretion of digestive enzymes of necrosis acinar cells [ 32 , 33 ]. Inhibition of this could effectively reduce the inflammatory response and relieve the progression of AP [ 15 ]. Hence, it is vitally important to search for effective and therapeutic target drugs to reduce acinar cell necrosis both in basic research and in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing numbers of researchers have shown that necroptosis, a new concept of necrosis, is regulated by the RIP kinase family, including receptor interacting protein 3 (RIP3) and downstream molecule lineage kinase domain-like protein (MLKL), which are involved in the regulation of several inflammatory processes, including myocardial infarction [ 9 ], ischemia-reperfusion injury [ 10 ], inflammatory bowel disease [ 11 ], and chronic obstructive pulmonary disease [ 12 ]. Acinar cell necroptosis plays an important role in AP [ 13 15 ] and is related to the development of AP [ 16 ]. Notably, RIP3 deficiency or p-MLKL deletion could significantly reduce the acinar cell necroptosis induced by caerulein in AP mice [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…typical Western diet) are linked with increased PD risk [ 102 , 103 ], and TLR4 is central to the inflammation and endoplasmic reticulum stress resulting from high-fat or high-cholesterol diets [ 104 , 105 ]. Interestingly, high-fat diets specifically increase the expression of intestinal TLR4 [ 95 ], and exacerbate intestinal barrier dysfunction in a TLR4-dependent manner in rats with severe acute pancreatitis [ 106 ]. Such diets not only encourage the growth of gram-negative, LPS-producing bacteria [ 107 ], but also increase the amount of lipids and free fatty acids, dietary components which, by themselves, can modulate TLR4 signalling [ 108 ] or rely on TLR4-priming for consequent lipid-induced inflammation [ 109 ].…”
Section: Tlr2 and Tlr4 Regulate Interactions Between The Gut Microbiome And Intestinal Barriermentioning
confidence: 99%